1993
DOI: 10.1111/j.1600-051x.1993.tb00351.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Acacia arabica gum on the in vitro growth and protease activities of periodontopathic bacteria

Abstract: The antibacterial activity of acacia gum was assessed using fresh isolates and reference strains of Actinobacillus actinomycetemcomitans, Capnocytophaga spp., Porphyromonas gingivalis, Prevotella intermedia and Treponema denticola. A fine aqueous suspension of gum was produced by sonication and then a soluble fraction isolated by centrifugation and membrane filtration. These preparations were incorporated into columbia agar at doubling concentrations. Growth of P. gingivalis and P. intermedia cultures on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 19 publications
0
47
0
1
Order By: Relevance
“…22 Therefore, the in vitro inhibitory action of acacia gum against these organisms and their enzymes is of possible clinical significance. 9 This inhibitory effect on periodontal pathogens along with the inhibition of protease production by them can be attributed to active constituents like arabica, cyanoglycosides, oxidases, peroxidase and pectinases present in Acacia. 7,8 Tannins are also found to be present in Acacia leading to its astringent and haemostatic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Therefore, the in vitro inhibitory action of acacia gum against these organisms and their enzymes is of possible clinical significance. 9 This inhibitory effect on periodontal pathogens along with the inhibition of protease production by them can be attributed to active constituents like arabica, cyanoglycosides, oxidases, peroxidase and pectinases present in Acacia. 7,8 Tannins are also found to be present in Acacia leading to its astringent and haemostatic effects.…”
Section: Discussionmentioning
confidence: 99%
“…8 Clark et al has reported the antibacterial and antiprotease activities of Acacia arabica. 9 Thus, the present study was carried out as a prospective, randomized, placebo and positively controlled clinical trial designed to evaluate the short-term clinical effects of a commercially available, prescription gel containing Acacia arabica in the reduction of plaque and gingival inflammation in subjects with gingivitis.…”
Section: Introductionmentioning
confidence: 99%
“…As for the antimicrobial activity of GA, few studies have been performed, mainly reporting growth inhibitory activity of certain periodontal pathogenic species (causal agent of tooth decay or agent involved in the plaque), such as Prophyromonas gingivalis and Prevotella intermedia (Clark et al, 1993). These results suggested that GA could inhibit the formation of plaque and improve dental remineralization, acting as a potential preventive agent in the formation of caries (Onishi et al, 2008).…”
Section: Antimicrobial Actionmentioning
confidence: 99%
“…A similar trend in disease protection was evident under field conditions, where seed treated with A. arabica gum offered highest disease control-protection of 48%, which was further increased to 96% when seed was treated with A. arabica+3 g kg −1 of metalaxyl 35 SD. Assessment of the antibacterial activity of acacia gum suggested that it has great clinical value (Clark et al 1993).…”
Section: Discussionmentioning
confidence: 99%